Investigational eIF2B activator DNL343 modulates the integrated stress response in preclinical models of TDP-43 pathology and individuals with ALS in a randomized clinical trial - Brittany N. Flores; Seungyoon B. Yu; Isaac V. Cohen; Melania H. Fanok; Wei Luan; Romeo D. Maciuca; Linus D. Sun; Richard M. Tsai; Maurits Vissers; Lars Smits; Tommy M. Bunte; Anna Bakardjiev; et al. (Nature Communications)
Abstract Neuronal TDP-43 aggregates are a hallmark ALS pathology. The integrated stress response (ISR) occurs downstream of TDP-43 pathology and may promote neurodegeneration. Here we demonstrate that a CNS penetrant small molecule eIF2B activator inhibits the ISR in cellular models of ALS and the brain of an inducible mouse model of TDP-43 pathology, where it transiently slowed progression of locomotor deficits and neurodegeneration. ISR activation was observed in ALS patient spinal cord and CSF. The investigational drug DNL343 was advanced into Phase 1 and Phase 1b randomized, double-blind, placebo-controlled trials in healthy and ALS participants, respectively (NCT04268784/NCT05006352); the primary objective in both studies was to investigate the safety and tolerability DNL343. DNL343 demonstrated a half-life supporting once-daily dosing and showed extensive CSF distribution. DNL343 was generally well tolerated and reduced ISR biomarkers in peripheral blood mononuclear cells and CSF of ALS participants. Therefore, DNL343 is a useful investigational drug to explore the effects of ISR inhibition in ALS models and individuals with neurological diseases.